Assessing the reliability and quality of content on social media regarding biologic therapies for psoriasis: A cross-sectional content analysis - Jianghui Li; Jiaying Fu; Qin Sun; Huanhuan Lei; Jiayun Li; Qinye Li; Yu Wang; Jiashui Hu; Xiaoning Yan (PLoS ONE, 2026)
Background Biologic agents are an important novel therapeutic option for moderate-to-severe psoriasis. In recent years, TikTok and Bilibili have gradually become important channels for Chinese patients to obtain health information. This study aims to evaluate the content, quality, reliability, and transparency of videos related to biologic therapy for psoriasis on these platforms. Methods We searched both platforms using the dual keywords “psoriasis” and “biological agents,” confirmed compliance with relevant criteria, and collected the top 150 videos based on their composite rankings. Fundamental characteristics, uploader categories, and content types were documented. Two independent reviewers evaluated video quality using the mDISCERN, GQS, and the JAMA criteria. Nonparametric tests were performed for group comparisons, and Spearman correlation analysis was applied. Results Bilibili videos more frequently addressed medical expenses, types of biologic agents, and recurrence, whereas TikTok videos focused on etiology and clinical manifestations. The video quality was barely acceptable. On TikTok, the median GQS, mDISCERN, and JAMA scores were 3.00 (2.25, 4.00), 3.00 (3.00, 4.00), and 2.00 (2.00, 3.00). On Bilibili, the median scores were 3.00 (2.00, 4.00), 3.00 (2.00, 4.00), and 1.00 (1.00, 3.00). Videos uploaded by professional organizations achieved the highest GQS (median 4.00, IQR: 4.00–4.00) but had the lowest engagement. Engagement metrics showed a moderate correlation with quality scores ( P < 0.05). Conclusions This study found that videos related to biologic therapy for psoriasis lack content completeness, with overall quality, reliability, and transparency remaining at a suboptimal level. Greater participation by professional organizations and increased visibility of their videos should be encouraged to promote the dissemination of high-quality content. This study provides preliminary insights for health communication strategies and highlights the necessity of strengthening content regulation.